Difference in Orthodontic Patients' Perceptions of Essix and Hawley Retainers - Putri I. Kusumawardhani; Krisnawati E. Tarman; Benny M. Soegiharto (Association of Support to Oral Health Research (APESB), 2021)
Objective: To determine differences in how orthodontic patients perceive the aesthetics relating to the use of Essix and Hawley retainers. Material and Methods: Photographs of a female patient using an Essix retainer and a Hawley retainer, respectively, were assessed by 70 orthodontic patients aged between 21 and 55 years. All participants were provided with the same images of the two retainer types being worn and were asked to grade the aesthetics of each retainer using a visual analog scale. The significance of differences in orthodontic patient perceptions of aesthetics in the use of Essix and Hawley Retainers in the young adult and adult age groups were tested using the Mann-Whitney test with assumed significance p<0.01. Results: There were differences in participants' perceptions between the two retainers that were statistically significant, with responses varying between young adults aged 21 to 35 years and adults aged 36 to 55 years. According to the VAS, the two retainers' average scores in the total population are 82 for Essix Retainer and 60 for Hawley Retainer in both groups. Conclusion: The Essix retainer as a retention appliance is considered more aesthetically pleasing than the Hawley retainer among both young and middle-aged adults.